100 UMPSA athletes to compete in 10 events at the 2024 SUKUM Championship - Siti Nur Azwin, Zulkapri (UMPSA, 2024)
PEKAN, 6 August 2024 – The enthusiastic cheers of “UMPSA! Minda Juara!” echoed as 100 athletes, comprising 65 men and 35 women from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), prepared to represent their university in the upcoming 2024 SUKUM Championship.